From a critique to self-evolving (inter)discipline: Critical geopolitics vs. popular geopolitics - Marta Zorko; Dario Sršen (Međunarodni Problemi)
The paper shows the development of critical geopolitics from its conceptualisation by O Tuathail, Dalby and Routledge at the end of the last century up to its critics and development of phenomena that influenced the self-evolution of discipline. The first goal of this research is the analysis of the main thesis from the abovementioned authors in order to test them on contemporary examples. The second goal is consisted of the contemporary phenomena analysis, from the media critique to a wider societal critique, as well as their influence on the self-evolution of the discipline, especially in the area of popular geopolitics. This review streams towards the state of the art analysis, defining and positioning this (inter)discipline in frames of old/new geopolitics, international relations, and human geography. The main thesis is that contemporary phenomena (as a cause) narrowed down the focus of research areas in some scientific fields, while in others it made unavoidable to skip interdisciplinary perspective both in theoretical as well as in methodological sense. The critics of classical geopolitics developed three directions for research: as a part of critical geopolitics as self-contained discipline and numerous subdisciplines or even disciplines (e.g., popular geopolitics); as critiques of newly developed neoclassical theories and schools in international relations; and as interdisciplinary attempts that highlights research on contemporary phenomena and criticise all so far developed methods and tools as nonadequate for research in such a complex world of the present challenges.